DIGITALISASI SISTEM PEMBAYARAN DALAM MEMPERKUAT SISTEM EKONOMI CAMPURAN DI INDONESIA: TINJAUAN LITERATUR - Aprilianti, Berty (Integrative Perspectives of Social and Science Journal, 2026)
This study examines how payment-system digitalization strengthens Indonesia’s mixed economy using Transaction Cost Economics and two-sided market and network-effects theory. Digital payments mobile and internet banking, e-wallets, QRIS, payment gateways, and instant transfers are treated as economic infrastructure that reduces frictions and broadens participation. A qualitative literature review synthesizes central-bank policy documents, payment statistics, and national and international studies. The synthesis identifies three reinforcement pathways: market efficiency, as faster, cheaper transactions lower time and operating costs and increase trading activity; inclusion and equity, as digital acceptance expands access for MSMEs and underserved users; and transparency, as recorded transactions support business planning, credit assessment, and policy accountability. In this context, the state advances standardization, interoperability, oversight, and consumer protection, while industry drives innovation and merchant expansion. Barriers persist literacy gaps, uneven connectivity, cyber fraud and trust risks, merchant fee perceptions, and ecosystem fragmentation calling for consistent, inclusive governance to sustain adoption and spread benefits nationwide.